Does the Internet Kill the Distance? Evidence From Navigation, E-Commerce, and E-Banking - Guido De Blasio (European Regional Science Association (ERSA), 2006)
By diminishing the cost of performing isolated economic activities in isolated areas, information technology might serve as a substitute for urban agglomeration. This paper assesses this hypothesis by using Italian household level data on internet navigation, e-commerce, and e-banking. Empirically, I find no support for the argument that the internet reduces the role of distance. My results suggest that: (1) Internet navigation is more frequent for urban consumers than their non-urban counterparts. (2) The use of e-commerce is basically not affected by the size of the city where the household lives. Remote consumers are discouraged by the fact that they cannot see the goods before buying them. Leisure activities and cultural items are the only goods and services for which e-commerce is used more intensively in isolated areas. (3) E-banking bears no relationship with city size. In choosing a bank, non-urban customers evaluate personal acquaintances as an important factor more intensively than urban clients. This also depends on the fact that banking account holders in remote areas are more frequently supplied with a loan by their bank.
Keywords: 330